RESILIENSI KOMUNITAS PETANI KOPI ARABIKA GAYO DI KABUPATEN BENER MERIAH PROVINSI ACEH PADA MASA PANDEMI COVID-19 - Husaini; Ishar; Arrozi, Ahmad Makki; Andriani, Rini; Rahly, Fawwa (Analisis Kebijakan Pertanian, 2024)
The COVID-19 pandemic that hit the world since early 2020 has caused some of economic sectors in the country declined. The agricultural sector has also been affected, including the Gayo Arabica coffee, which has reduced production level, selling value, and has the potential to decrease farmers income. Farmers must have a good adaptive capacity to survive and recover from these shocks. This study aims to analyze the adaptations made by Gayo Arabica coffee farmers during the COVID-19 pandemic. This research was conducted in Pondok Gajah Village, Bener Meriah District, Aceh Provbonce, in September 2020. A purposive non-probability sampling method was used in this research. Primary data was collected through interviews using a questionnaire. A descriptive qualitative analysis was used, along with the Longstaff theory approach related to adaptive capacity using the economic subsystem framework. The results showed that the effective adaptation strategy adopted by Gayo Arabica coffee farmers during the COVID-19 pandemic focused only on an innovative learning aspect and relied solely on by-products activity such as intercropping with tomatoes, chilies, cabbage and potatoes among coffee plants. This adaptation strategy is only a short-term mechanisms to overcome the potensial falling income from coffee farming. Government support is needed in the form of a policy of easy access to capital so that farmers can postpone selling coffe beans to overcome marketing difficulties.